Unexpected High Sensory Blockade during Continuous Spinal Anesthesiology (CSA) in an Elderly Patient - R. Ketelaars; A. P. Wolff (Case Reports in Anesthesiology)
A 98-year-old woman presented for a hemiarthroplasty of the left hip. Because of her age and cardiac and pulmonary co-existing diseases we decided to provide adequate regional anesthesia by continuous spinal anesthesia. Fragmented doses of isobaric bupivacaine 0.5% were administered through a system consisting of a spinal catheter connected to an antimicrobial filter. After an uneventful surgical procedure, prior to removal of the catheter, this system was flushed with 10 mL of normal saline in order to try to prevent post-dural-puncture headache. After arrival at the postanesthesia care unit and fifteen minutes after removal of the catheter the patient suffered an unexpected high thoracic sensory blockade and hypotension requiring treatment. The continuous spinal anesthesia technique can be used in selected cases to be able to administer local anesthetic agents in a slow and controlled manner to reach the desired effect. The risk of post-dural-puncture headache using this technique in elderly patients is very low and therefore precludes the need to try to prevent it. We have described a potentially dangerous complication of flushing a bupivacaine-filled system into the spinal canal of an elderly patient resulting in an undesirable high sensory blockade.